Hipertensi pada Obesitas Masa Anak - Mexitalia Mexitalia; M Herumuryawan; M Sakundarno; Hertanto Wahyu Subagio; Agustinus Soemantri (MEDIA MEDIKA INDONESIANA, 2010)
Background: The prevalence of obesity in children increased rapidly in recent years. One of the comorbidity of obesity is the premature onset of cardiovascular risk factors such as hypertension. The objective of the study is to describe the relationship between obesity and the elevated of blood pressure in children.Method: The population for this cross-sectional study was students in one of the junior high school in Semarang with the mean age of 13.5 years. The anthropometric and blood pressure data were taken in 2006. BMI was measured with bioelectrical impedance analysis (BIA) Omron Karada Scan and classified based on International Obesity Task Force according to CDC 2000 graphs. The blood pressure was measured by using Omron Digital type SEM-1 and classified based on national high blood pressure education program (NHBPEP). Anova, Spearman correlation and chi-square test were performed to analyze the data.Result: Of 1.129 students (50.7% boys and 49.3% girls), 185 (16.4%) were overweight and 160 (14.2%) were obese. Hypertension was detected in 304 students (26.9%). There were significant correlation between systolic blood pressure with BMI (r=0.466) and diastolic blood pressure with BMI (r=0.337). The risk to hypertension in overweight was 2.8 times greater (OR=2.79; 95% CI 1.97-3.96 p<0.001) and in obesity was 6.6 times greater (OR=6.61; 95% CI 4.59-9.52 p0.001) than normoweight children. Chinese race has 1.4 times greater risk to have hypertension than native Indonesian children.Conclusion: Overweight and obeis children have greater risk for hypertension than normal children. AbstrakLatar belakang: Prevalensi obesitas pada anak meningkat pesat dalam beberapa tahun terakhir. Salah satu komorbiditas obesitas yang terjadi sejak dini adalah penyakit kardiovaskuler seperti hipertensi. Tujuan dari penelitian ini adalah mengetahui hubungan antara obesitas dengan peningkatan tekanan darah pada anak.Metode: Desain penelitian adalah belah lintang dengan populasi adalah siswa sebuah SLTP di kota Semarang dengan rerata umur 13,5 tahun. Pengambilan data antropometri dan tekanan darah dilakukan tahun 2006. Indeks massa tubuh (IMT) diukur Bioelectrical Impedance Analysis (BIA) Omron Karada Scan dan status gizi ditetapkan berdasarkan kriteria International Obesity Task Force dengan memakai grafik CDC 2000. Tekanan darah diukur dengan Omron Digital type SEM-1 dan ditetapkan berdasarkan klasifikasi National High Blood Pressure Education Program (NHBPEP), dinyatakan hipertensi bila tekanan darah >persentil ke-90. Data dianalisis dengan Anova, Spearman correlation dan chi-square. Hasil: Dari 1.129 siswa (50,7% laki-laki dan 49,3% perempuan), 185 (16.4% adalah gizi lebih dan 160 (14,2%) obesitas. Didapatkan 304 siswa (26,9%) dengan hipertensi. Terdapat korelasi signifikan antar IMT dengan tekanan darah sistolik (r=0,466) dan tekanan darah diastolik (r=0,337). Risiko untuk terjadi hipertensi meningkat 2,8 kali (OR=2,79; 95% CI 1,97-3,96 p<0,001) pada anak dengan gizi lebih dan 6,6 kali (OR=6,61; 95% CI 4,59-9,52 p0,001) pada anak dengan obesitas. Ras Tionghoa mempunyai risiko 1,4 kali lebih tinggi untuk terjadi hipertensi dibandingkan pribumi.